Exogenous Neural Stem Cells Affect the Post-Ischemic Nerve Tissue In Vitro - Rybachuk, Oksana A.; Kyryk, Vitaliy M.; Tsupykov, Oleg M.; Butenko, Gennadiy M.; Skybo, Galina G.; Pivneva, Tatyana A. (Problems of Cryobiology and Cryomedicine, 2013)
N/AProbl Cryobiol Cryomed 2013; 23(4):363–367.